Reflections on Quantitative Fiscal Conditionality in African PRGF-Supported Programs - Zakharova, Daria (IMF Working Papers; Working Paper, 2006)
We survey quantitative fiscal conditionality in selected sub-Saharan African PRGFsupported programs, and assess the conditionality against some possible benchmarks and best practices. While noting many caveats, the paper suggests some possible scope for further attuning of this conditionality to countries' specific macro-fiscal situations. The paper also offers some suggestions on how quantitative fiscal conditionality might be further enhanced.